Processos colaborativos e a reconfiguração da docência alfabetizadora a partir do laboratório de mudanças - Ventorini, Rosani Dutra (2023)
This research is linked to the Postgraduate Program of the Academic Master's Degree Course of the Federal University of Santa Maria in the Research Line LP1 Teaching, Knowledge and Professional Development, from the Research Group Practices and Training for Teaching: Basic and Higher Education (GPDOC). It aims to understand the reconfiguration of literacy teaching based on collaborative reflective processes, with the following specific objectives: (i) to identify the challenges and vulnerabilities of the teaching activities of literacy teachers; (ii) to recognize the training demands that are necessary to boost teachers' pedagogical mediations with the groups with which they work; (iii) to understand the processes involved in collaborative reflection and their implication in the reconfiguration of literacy teaching. The discussions cover the situation of literacy in Latin America and Brazil, its historical nuances and the effects of the Covid-19 pandemic, as well as the possibilities for dealing with it by strengthening a collaborative culture that favors the daily work of teachers in schools, impacting the pedagogical practices to be developed in the classroom. Thus, we highlight the fabric of literacy teaching, focusing on the interactive nature of teaching work and its development, identifying aspects capable of boosting pedagogical protagonism in the school context. The methodological procedure of the investigation was the Change Laboratory, which has been used in several areas to reconfigure their activities, but there is still little use in the field of teacher training. In this study, this methodology was developed with eight teachers working in the early years of primary education at a primary school in the municipality of Santa Maria. The study made it possible to identify prevalent dimensions in the reconfiguration of literacy teaching, which are related to the challenges of literacy practices, which, when analyzed and problematized collectively, highlight contradictions and vulnerabilities faced by teachers, allowing the identification of germ cells related to the process of qualifying the ongoing literacy practices. In this sense, the power of the collectivity in the school context emerges as a potential element for reconfiguring literacy teaching. Thinking as a school immersed in a collaborative environment has the power to strengthen bonds between teachers, mitigate teaching and structural vulnerabilities, and reduce teachers' feelings of powerlessness. For future research, it is suggested to continue using this methodology with the aim of creating an in context training environment within schools and organized by the teachers themselves.